THE EFFECT OF TUITION FEES ON STUDENTS' DECISION TO CHOOSE A COLLEGE - Zuhra, Ziyanatuz; Aisyah, Siti; Astuti, Sri (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the influence of education costs on students' decisions in choosing higher education institutions, with a case study on Universitas Islam Indragiri students batch 2024. The research background is based on the challenges of higher education accessibility in Indonesia, particularly in Indragiri Hilir Regency, Riau Province, which are influenced by cost factors, economic disparities, and infrastructure limitations. The research method used is quantitative with a survey approach involving 93 randomly selected respondents from a population of 1,235 students. Data were collected through questionnaires and analyzed using simple linear regression, t-test, and coefficient of determination test. The results show that education costs have a significant influence on students' decisions in choosing higher education institutions, with a t-value (9.047) > t-table (1.662) and a significance level of 0.000 < 0.05. However, economic income does not have a significant influence (significance level 0.591 > 0.05). The most considered component of education costs is the funding source, with the highest average score (4.12). The majority of students rely on parental funding (52.7%), while 24.7% combine self-funding with family support. The implications of this study emphasize the importance of transparent and affordable education cost policies, as well as expanding scholarship access to increase higher education participation. This research also recommends the need for more equitable socialization of education funding programs to prospective students.